Empire and Superempire : Britain, America and the World - Porter, Bernard (New Haven Yale University Press., 2006)
"How alike are the American and British empires really? What are the connections between them? And what can we learn from the comparison? In this book, a historian of the British empire explores these questions in depth for the first time. Bernard Porter finds that Britain and America had uncannily similar imperial histories before the present day, but that now considerable differences exist. He argues that post-2001 American imperialism is an imperialism of a different sort - a 'super-imperialism' that no longer repeats British imperialism but now transcends it."--Jacket.
Include Conclusion and Index
Keywords: United States -- Foreign Relations -- 2001-2009 -- Great Britain -- Foreign Relations -- 1997- -- United States -- Foreign Relations